Aksjologiczne podstawy ubezpieczeń społecznych - Rogowski, Robert (Annales. Etyka w Życiu Gospodarczym, 2009)
The article emphasizes axiological and moral foundations of national insurance system. The most fundamental values connected with the insurance system are presented. It is illustrated how the moral values can be realized with the economics solutions such as retirement insurance and health insurance systems. The final aim of insurance system is to protect human dignity.